2023
DOI: 10.1038/s41564-023-01405-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling viral encephalitis caused by herpes simplex virus 1 infection in cerebral organoids

Abstract: Herpes simplex encephalitis is a life-threatening disease of the central nervous system caused by herpes simplex viruses (HSVs). Following standard of care with antiviral acyclovir treatment, most patients still experience various neurological sequelae. Here we characterize HSV-1 infection of human brain organoids by combining single-cell RNA sequencing, electrophysiology and immunostaining. We observed strong perturbations of tissue integrity, neuronal function and cellular transcriptomes. Under acyclovir tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…These cells were infected with HSV-1 and -2, and we performed transcriptome analysis. Consistent with published data from human fibroblasts 36 and brain organoids, 37 transcription termination was also disrupted in ESC-derived neurons and resulted in transcriptional shutoff. Importantly, we found that expression of IFN signaling pathways as well as HIF target genes was disrupted upon HSV infection ( Figures 1 F–1G, S3 K, and S3L).…”
Section: Resultssupporting
confidence: 91%
“…These cells were infected with HSV-1 and -2, and we performed transcriptome analysis. Consistent with published data from human fibroblasts 36 and brain organoids, 37 transcription termination was also disrupted in ESC-derived neurons and resulted in transcriptional shutoff. Importantly, we found that expression of IFN signaling pathways as well as HIF target genes was disrupted upon HSV infection ( Figures 1 F–1G, S3 K, and S3L).…”
Section: Resultssupporting
confidence: 91%
“…A strong transcriptional activation of the innate immune response had also been observed in our RNA-seq datasets from HSV-1 infection in dcOrgs and also reported previously from HSV-1 infection in 3D cerebral organoids 41 . This innate immune response is most likely produced by microglia or astrocytes within the cerebral organoids, although a small fraction (∼3%) of neurons had been reported to produce type I interferon response 77 .…”
Section: Resultssupporting
confidence: 89%
“…The use of a combinatorial drug therapy, including acyclovir with antiinflammatory drugs (necrostatin-1 or bardoxolone methyl) prevented virus replication and associated BBB damage. 39 This suggests that controlling the inflammatory response at an acute stage of infection may improve HSV-1-induced neurovirulence. As the induction of inflammatory response at the BBB interface is a hallmark feature of most neurotropic viruses, the use of inflammatory drugs together with virus-specific antiviral may halt neuroinvasiveness caused by other neurotropic viruses.…”
Section: Blocking the Degradation Or Mislocalization Of Junctional Pr...mentioning
confidence: 99%
“…Treatment with acyclovir, an antiviral drug against HSV‐1, repressed virus replication, but did not protect from BBB disruption which is driven by TNFSF members activation during HSV infection. The use of a combinatorial drug therapy, including acyclovir with anti‐inflammatory drugs (necrostatin‐1 or bardoxolone methyl) prevented virus replication and associated BBB damage 39 . This suggests that controlling the inflammatory response at an acute stage of infection may improve HSV‐1‐induced neurovirulence.…”
Section: Approaches To Prevent Viral Neuroinvasionmentioning
confidence: 99%